Crowdsourcing, sharing economy and development - TAEIHAGH, Araz (Institutional Knowledge at Singapore Management University, 2017)
What are the similarities and differences betweencrowdsourcing and sharing economy? What factors influence their use indeveloping countries? In light of recent developments in the use of IT-mediatedtechnologies, such as crowdsourcing and the sharing economy, this manuscriptexamines their similarities and differences, and the challenges regarding theireffective use in developing countries. We first examine each individually andhighlight different forms of each IT-mediated technology. Given that crowdsourcingand sharing economy share aspects such as the use of IT, a reliance on crowds,monetary exchange, and the use of reputation systems, we systematically comparethe similarities and differences of different types of crowdsourcing with the sharingeconomy, thus addressing a gap in the current literature. Using this knowledge,we examine the different challenges faced by developing countries when using crowdsourcingand the sharing economy, and highlight the differences in the applicability ofthese IT-mediated technologies when faced with specific development issues.